2021
DOI: 10.1002/app.50831
|View full text |Cite
|
Sign up to set email alerts
|

Water‐repellent films from corn protein and tomato cutin

Abstract: Flexible and hydrophobic biobased films were obtained using zein esterified with methanol and para-toluene (p-toluene) sulfonic acid, cutin from tomato peels and ethanol. Esterification was confirmed by proton nuclear magnetic resonance and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). Non-modified zein films were brittle and hydrophilic. ATR-FTIR demonstrated that zein esterification increased zein hydrophobicity. Without cutin, esterified zein films were hydrophobic but bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To further confirm the successful grafting of SA onto AM-zein, the structures of AM-zein, AM-zein-SA, and SA were further characterized by 1 H NMR spectroscopy. Figure 6 shows the 1 H NMR spectra of AM-zein, AM-zein-SA, and SA in deuterated-DMSO solvent, where the sharp proton signal at δ = 2.43 was due to the proton peak of deuterated-DMSO, peak at δ = 3.49 in AM-zein was attributed to the proton of free primary amine [ 43 ], and peaks between δ = 0−3.2 corresponded to the proton signals of 19 aliphatic amino acids that make up the zein molecule [ 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the successful grafting of SA onto AM-zein, the structures of AM-zein, AM-zein-SA, and SA were further characterized by 1 H NMR spectroscopy. Figure 6 shows the 1 H NMR spectra of AM-zein, AM-zein-SA, and SA in deuterated-DMSO solvent, where the sharp proton signal at δ = 2.43 was due to the proton peak of deuterated-DMSO, peak at δ = 3.49 in AM-zein was attributed to the proton of free primary amine [ 43 ], and peaks between δ = 0−3.2 corresponded to the proton signals of 19 aliphatic amino acids that make up the zein molecule [ 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the spectral bands at 1701, 1170 cm −1 are assigned to the C=O in ester groups; the spectral band at 1032 cm −1 is assigned to the glycosidic linkages (C-O-C) stretching, implying that the saccharides and lignin co-existed [ 33 ]. Combined with the conclusion of HSQC, it can be concluded that the LCCs are one main form of lignin in membrane foulant, which is consistent with the current literature [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Corn, with a protein content of approximately 10%, exhibits varying protein distributions, with 20% in the germ and 76% in the endosperm . Corn protein is mainly made up of zein (65%–68%) and gluten (22%–23%), with small amounts of globulin and albumin (1.2%).…”
Section: Sources Of Plant Proteinmentioning
confidence: 99%
“…10 Corn, with a protein content of approximately 10%, exhibits varying protein distributions, with 20% in the germ and 76% in the endosperm. 11 Corn protein is mainly made up of zein (65%−68%) and gluten (22%−23%), with small amounts of globulin and albumin (1.2%). Corn protein has poor water solubility due to its high hydrophobic amino acid content, which limits its application as a supplementary nutrient.…”
Section: Sources Of Plant Proteinmentioning
confidence: 99%